Piazza degli eroi di Thomas Bernhard: l’uomo, il tempo e la storia: Intervista a Roberto Andò - Sapienza, Annamaria (Mimesis Journal, 2021)
The script is an interview with Roberto Andò, director and author among the most versatile of the Italian and European scene. In late 2020 Andò directed Heroes' Square (1988) by Thomas Berhard. The show should have been staged at the Mercadante theatre in Naples, of which he is the director, but the restrictions related to the medical emergency prevented its representation some time later. The show was then streamed by Rai 5 in a program that, in an attempt to keep the attention on a world among the most penalized by the pandemic, has made a series of television shows. The result was a of public and critical success, unexpected as hoped, which offered the opportunity to analyze this transcoding, opening a delicate issue on the compromise of the theater with the medium of television. The interview retraces the journey of Thomas Bernhard and his arrival in Heroes' Square that seems destined to create a «case» that goes beyond its representation.